2020
DOI: 10.1097/hrp.0000000000000273
|View full text |Cite
|
Sign up to set email alerts
|

Negative Symptoms and Functioning in Youth at Risk of Psychosis: A Systematic Review and Meta-analysis

Abstract: Aim: Youth at clinical high risk for psychosis often demonstrate significant negative symptoms and poor functioning. However, the magnitude and direction of the relationship between the two remains unknown. Therefore, the objective of this systematic review was to summarize the relationship between negative symptoms and functioning in CHR samples.Method: Electronic databases Embase, EBM, MEDLINE, CINAHL, and PsycINFO were searched from inception. Studies were selected if they included any study that reported a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 103 publications
2
15
0
Order By: Relevance
“…Such results suggest that the abnormal myelination found in our study could underlie poorer functioning and faster functional drop, as well as more severe negative symptoms prior to the onset of psychosis. Largely in line with previous studies, it is recognised that negative symptoms are commonly presented at the premorbid phase of psychosis and are frequently associated with poorer functioning, more cognitive impairments, and worse long-term outcome, especially in youth at CHR of psychosis 32. Since negative symptoms have been conceptualised as the insufficient communication between brain regions, the disrupted myelin found in our CHR sample could underlie the insufficiency of information communication and integration between hemispheres, which subsequently gives rise to negative symptoms.…”
Section: Discussionsupporting
confidence: 77%
“…Such results suggest that the abnormal myelination found in our study could underlie poorer functioning and faster functional drop, as well as more severe negative symptoms prior to the onset of psychosis. Largely in line with previous studies, it is recognised that negative symptoms are commonly presented at the premorbid phase of psychosis and are frequently associated with poorer functioning, more cognitive impairments, and worse long-term outcome, especially in youth at CHR of psychosis 32. Since negative symptoms have been conceptualised as the insufficient communication between brain regions, the disrupted myelin found in our CHR sample could underlie the insufficiency of information communication and integration between hemispheres, which subsequently gives rise to negative symptoms.…”
Section: Discussionsupporting
confidence: 77%
“…Negative symptoms are often the first symptoms that CHR-P individuals develop (Metzak et al ., 2020 ). There is a strong negative relationship between negative symptoms and functioning in CHR-P individuals (Devoe et al ., 2020 ; Metzak et al ., 2020 ), a finding also confirmed in individuals with schizophrenia (Ventura et al ., 2009 ). Therefore, the observed clinical improvements in the severity of core CHR-P symptoms were paralleled by functional improvements at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important finding as both negative symptoms and social functioning are considered the hardest to treat. Although some recent meta-analytic evidence showed small effects of cognitive behaviorally informed interventions on negative symptoms 38,39 and functioning 38 in individuals with psychosis, two meta-analyses specifically focusing on youth at clinical high risk for psychosis concluded that, currently, no effective treatments are available for either improving functioning 40 or ameliorating negative symptoms 41 in the early stages of psychosis. Yet, negative symptoms are considered the most disabling symptoms 42,43 , being closely associated with lower levels of functioning and higher risk for a more disabling course of illness.…”
Section: Discussionmentioning
confidence: 99%